Peer Victimization Influences Attention Processing Beyond the Effects of Childhood Maltreatment by Caregivers - Iffland, Benjamin; Neuner, Frank (Frontiers in Psychology, 2022)
Background: Different types of maltreatment (emotional, physical, sexual) lead to distortions in emotion and attention processing. The present study investigated whether the experience of peer victimization in childhood and adolescence has an additional influence on attention processing in adulthood. Methods: Two non-clinical samples consisting of individuals with different levels of experiences of maltreatment were recruited. In an evaluative conditioning task, images of faces with neutral emotional expression were either associated with short videos of intense negative statements, or associated with neutral videos. Subsequently, these faces were used as stimuli in an Emotional Stroop task as well as a dot-probe task. Results: In both tasks, hierarchical regression analyses revealed that retrospective reports of relational peer victimization made an incremental contribution to the prediction of attentional biases beyond child maltreatment. In the Emotional Stroop task, emotional abuse was the strongest predictor for an attentional bias showing delayed responses to negatively associated faces, while peer victimization was associated with faster responses to negatively associated faces. In the dot-probe task, relational peer victimization was the strongest predictor for an attentional bias. When the attentional bias was examined in more detail, though, peer victimization did not show incremental contributions although emotional abuse remained the strongest predictor for facilitated attention towards negatively associated neutral faces. Conclusion: Experiences of peer victimization leave additional cognitive scars beyond effects of childhood maltreatment by caregivers. It is likely that attentional biases in the aftermath of victimization put individuals at risk for the development of psychopathology.